The burden of antenatally undiagnosed major congenital anomalies in live-born babies at a busy secondary level maternity hospital in the Western Cape - Amankrah, Melvin (Department of Paediatrics and Child Health, 2025)
Background: Major congenital anomalies (MCA) account for considerable morbidity and disability in South Africa (SA) where there is a predicted birth prevalence of 27.5/1000 live births. There are limited data on MCA prevalence and impact on neonatal services in SA, especially the Western Cape province. Objective: To determine the prevalence, characteristics, and short-term outcomes of antenatally-undiagnosed neonates with MCA at Mowbray Maternity Hospital (MMH) in 2022. Methods: A retrospective, cross-sectional study of live-born neonates with MCA admitted to MMH neonatal services between 1 January- 31 December 2022. Stillbirths and antenatally diagnosed MCA neonates were excluded. Cases identified from the ward register and data collected by folder review using a standardized data collection form and analysed using R and Microsoft Excel. Continuous variables, described as medians and interquartile ranges, compared using the Wilcoxon rank sum test. Categorical variables presented as proportions and assessed using chi2test. Results: With 73 neonates included, the in-facility MCA prevalence rate was 36 per 1000 neonatal admissions and 6/1000 live MMH in-born infants. Most (82%) had a basic antenatal ultrasound and 29% a fetal anomaly scan. Syndromic MCA was present in 36% and non-syndromic MCA in 64%. Non-syndromic MCA included isolated genitourinary (21%), orofacial (19%), gastrointestinal (17%) and cardiovascular defects (15%). The most prevalent syndromic MCA was Trisomy 21 (58%). Syndromic MCA was significantly associated with advanced maternal age (³36 years), increased gravidity (³5) and low birth weight (<2500g), p < 0.001. The in-hospital mortality rate was 15%. Conclusion: In this single hospital-based study, the MCA prevalence was high among in-born and referred neonates. Diagnosis was not made antenatally despite a high proportion of women booking early and receiving antenatal ultrasound. Large collaborative registries and studies are recommended to establish the true impact of CA on children and their outcomes in SA.